Requirement Analysis of it for SCM and E Business and Challenges of Implementation: Understanding the Growth and Challenges of FMCG Sector in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The Indian FMCG sector with a market size of US14.8 billion is the fourth largest sector in the economy. The FMCG market is set to double from USD 14.7 billion in 2011-12 to USD 30 billion in 2013. FMCG sector will witness more than 60 per cent growth in rural and semi-urban India by 2014. Indian consumer goods market is expected to reach 400 billion by 2014.Hair care, household care, male grooming, female hygiene, and the chocolates and confectionery categories are estimated to be the fastest growing segments. At present, urban India accounts for 66 of total FMCG consumption, with rural India accounting for the remaining 34. However, rural India accounts for more than 40 consumption in major FMCG categories such as personal care, fabric care, and hot beverages.